THERMOHALOPHILIC BACTERIA PRODUCING THERMOSTABLE LIPASE FROM WAWOLESEA HOT SPRING, SOUTHEAST SULAWESI - Sapto Raharjo; Muzuni; Ardiansyah; Rahman Hakim; Muh. Musafir; Tien; L.O.M. Iman Sulaeman (BRIN - Badan Riset dan Inovasi Nasional, 2026)
This study aimed to isolate and characterize thermohalophilic bacteria producing lipase and to purify thermostable lipase from the Wawolesea hot spring in Southeast Sulawesi. A total of 24 isolates were obtained, all of which demonstrated lipase-producing capability. Three selected isolates (BT2.M3, CT2.M4, and DT1.M2) were identified as Gram-negative bacilli and showed lipase activities ranging from 0.17 to 21 U/mL, with the highest activity recorded for BT2.M3 at 50°C and pH 6. Purification through ammonium sulfate fractionation yielded the highest activity in the 60–80% saturation fraction (43 U/mL) at pH 6–7 and 50–60°C. Protein analysis showed the highest concentration in the 80% dialysis fraction (0.954 mg/mL). These findings highlight the potential of Wawolesea thermohalophilic bacteria as a valuable source of thermostable lipase for biotechnological applications.